2020
DOI: 10.1162/rest_a_00871
|View full text |Cite
|
Sign up to set email alerts
|

International Transfer Pricing and Tax Avoidance: Evidence from Linked Trade-Tax Statistics in the United Kingdom

Abstract: This paper employs unique data on export transactions and corporate tax returns of UK multinational firms and finds that firms manipulate their transfer prices to shift profits to lowertaxed destinations. It uncovers three new findings on tax-motivated transfer mispricing in real goods. First, transfer mispricing increases substantially when taxation of foreign profits changes from a worldwide to a territorial approach in the UK, with multinationals shifting more profits into low-tax jurisdictions. Second, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…It can imply that the size of the company weakens the amount of tax on transfer pricing. On the contrary, the smaller the company's size, the more effect of taxes on transfer pricing becomes positive.The findings of this study were able to successfully reaffirm the conclusions of previous research that had been conducted by Liu et al, (2020); Siregar and Utama (2005), had found that the size of the company harms transfer pricing.…”
Section: Discussionsupporting
confidence: 86%
“…It can imply that the size of the company weakens the amount of tax on transfer pricing. On the contrary, the smaller the company's size, the more effect of taxes on transfer pricing becomes positive.The findings of this study were able to successfully reaffirm the conclusions of previous research that had been conducted by Liu et al, (2020); Siregar and Utama (2005), had found that the size of the company harms transfer pricing.…”
Section: Discussionsupporting
confidence: 86%
“…A key focus of the literature on shifting to havens is in identifying the various shifting techniques. A variety of ways have been identified, including manipulating transfer prices between affiliates [Cristea & Nguyen 2016;Davies et al 2018;Liu et al 2020;Wier 2020], the strategic location of intellectual property [Dischinger & Riedel 2011;Karkinsky & Riedel 2012;Griffith et al 2014], international debt shifting [Fuest et al 2011;Buettner & Wamser 2013] and treaty shopping [Hong 2018;Riet & Lejour 2018]. We refer to Heckemeyer & Overesch (2017) and Beer et al (2020) for comprehensive surveys.…”
Section: Related Literaturementioning
confidence: 99%
“…Recent literature has uncovered effect heterogeneity in the profit shifting behavior of multinational entities. For example, profit shifting is concentrated in large multinationals (Wier and Reynolds, 2018), is stronger in R&D intensive firms (Liu et al, 2020) and to countries that impose low or no taxes on corporate profits (Dowd et al, 2017;Davies et al, 2018;Tørsløv et al, 2018). To explore the extent to which the impact of territorial tax reform may vary across these characteristics, we divide firms in the low-tax sample into quintiles (for each firm characteristic), and estimate the effect of the tax reform by interacting the policy variable with the quintile indicators.…”
Section: A2 Heterogeneity Analysismentioning
confidence: 99%
“…Empirical studies have analyzed the impact of a change in the international tax regime on various margins of firm behavior, including on dividend repatriation (Egger et al, 2015;Hasegawa and Kiyota, 2017), cash holding/dividend payout (Arena and Kutner, 2015), real investment (Liu, 2020), tax management (Kohlhase and Pierk, 2020) and mergers and acquisitions (Feld et al, 2016). 7 Focusing on international transfer mispricing as a particular channel of profit shifting, Liu et al (2020) find that the UK territorial tax reform reduced transfer prices on UK exports to low-tax countries by more than one third. Azémar and Dharmapala (2019) show that introducing a territorial tax system does not affect the value of tax sparring agreements (which prevent host country tax incentives from being nullified by home country taxes).…”
Section: Introductionmentioning
confidence: 99%